Le recouvrement de l'impôt et les droits de la personne - Brun, Henri (Les Cahiers de droit, 1983)
Those who like to pay tax are few. Accordingly, income tax is often described as a shame. Of course, the right to enjoyment of property is at stake in the matters of taxation. And the collection of taxation involves also other aspects of the right to substantive and procedural due process of law : right to privacy, to be heard, to unbiassed decision, to professional secrecy... This article contrasts these rights, as they are expressed in sections 5 to 9 and 23 of the Charte des droits et libertés de la personne of Québec and section 8 of the Canadian Charter of Rights and Freedom, with sections 13 to 16 and 38 and following of the Loi sur le ministère du revenu of Québec and sections 159, 231 and 232 of the Canadian Income Tax Act. It finds that it is the application of the income tax law, more than the law itself, that threatens human rights. It concludes that the main benefit of both Charters of rights is to provide a shelter from such unreasonnable application